الإجماع عند الإمام ابن رشد الحفيد من خلال كتابه بداية المجتهد ونهاية المقتصد كتاب الجنايات أنموذجا - مدلل, نجاح (University of Eloued-جامعة الوادي, 2016)
Note contains two chapters: the first chapter in my contains a translation of Ibn Rushd, the definition of his book" bidayet El Mojtahid" and includes a study of the fundamentals of the theory of consensus, and the second chapter application included a study models of doctrinal issues in which he said Ibn Rushd consensus limited to Alajmaat received formula "consensus" and "agreement" and denied the dispute "in the book of felonies from " bidayet El Mojtahid wa nihayet Almoktasid" , and Investigation is it a place of consensus, and are stating otherwise or not? with reference to this Alajmaat document. The most important results Ibn Rushd was accurate in the transfer Alajmaat rarely unanimity did not find a manual, and also Alajmaat contained form consensus and agreement tandem when Ibn Rushd often, but denied the dispute is intended "ibn Rushd" is the lack of knowledge Palmkhalv not science against the violator.
مذكرة ماستر
Keywords: الإجماع عند الإمام ابن رشد الحفيد/بداية المجتهد ونهاية المقتصد; Consensus according to Imam Ibn Rushd, the grandson / The beginning of the mujtahid and the end of the prudent